Growth dan Media Exposure terhadap Pengungkapan Islamic Social Reporting - Nur Wahyu Ningsih; Ruslan Abdul Ghofur; Ranny Aprilia Pratiwi (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2021)
This study is aims to examine the impact of growth and media exposure on Islamic Social Reporting disclosure. To measure the extent of Islamic social reporting, used a checklist that has been developed based on related rules and previous research. The research method used is this research is quantitative research methods, this method is called quantitative method because the research data in the form of numbers and analysis employed statistics. While for the type of data used in this study is secondary data, secondary data in this study in the form of annual report, sustainability report and financial statement companies listed on the Indonesian sharia stock index in 2016-2018. The method used in this research is quota sampling, There were 13 companies which fulfilled criterion as the research samples. The data collection method in this study is the documentation method, is collecting data from ISSI official website based on criteria and collecting data from the company’s official website. The results of this study showed that growth and media exposure no significant impact on Islamic Social Reporting.